Surgical and chemical castration induce differential histological response in prostate lobes of Mongolian gerbil - Goes, Rejane Maira; Zanetoni, Cristiani; Tomiosso, Tatiana Carla; Ribeiro, Daniele Lisboa; Taboga, Sebastiao Roberto (Elsevier B.V., 2007)
The present study describes the short-term alterations in the prostate ventral and dorsal lobe of the adult Mongolian gerbil, in response to two different androgen suppression approaches. Groups (n = 6) of 16-week-old gerbils were maintained intact or subjected, either to the bilateral surgical castration I week previously or to daily subcutaneous injections of Flutamide (10 mg/kg body weight) for 7 days. The main microscopic features of both prostate lobes in these groups were compared using conventional paraffin tissue sections, measurements of acinar epithelial height and stereological data of main gland components (acini, collagen fibers and fibromuscular stroma). Marked alterations were observed in the basement membrane of the ventral lobe after both surgical and chemical castration, such as an increase in thickness and collagen staining. A low degree of epithelial atrophy was detected in the dorsal lobe following both androgen suppression approaches in comparison with that found in the ventral lobe, indicating that this lobe is not so responsive to testosterone ablation induced by castration or Flutamide treatment, at least insofar as secretory activity is concerned. However, the dorsal lobe exhibited marked stromal modification, such as an increase in collagen fibers following castration and an increase in fibromuscular stroma following Flutamide-treatment. Thus, the histological and quantitative data indicates a differential short-term response of the prostate dorsal lobe to surgical castration and Flutamide therapy, suggesting the existence of lobe-specific mechanisms for stromal remodeling. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Mongolian gerbil; prostate ventral lobe; prostate dorsal lobe; orchiectomy flutamide; Anti-androgen